FIRST RECORD OF LECANE BIFURCA (BRYCE, 1892) (ROTIFERA, MONOGONONTA, LECANIDAE) FOR TURKISH INLAND WATERS - Bulut, Hilal (Parlar Scientific Publications (P S P), 2018)
The zooplankton fauna of Mamikan Stream was studied between May 2012-April 2013. During the study, total of 23 zooplankton species, 17 species from Rotifera, 4 species from Cladocera and 2 species from Copepoda were identified. Maximum number of zooplankton has been recorded in May (35648 individuals/m(3)). The least the number of individuals were recorded in February (2036 individuals/m(3)). Among all zooplankton were represented with Rotifera 74%, Cladocera 17% and Copepoda 9%. Lecane bifurca (Bryce, 1892), between the species identified was important as to new record in this region for Turkey rotifer fauna.
Keywords: Lecanidae; new record; stream; Turkey; zooplankton